The Impact Of Product Quality And Service Quality On Consumer Satisfaction At Kedai Falsafah Ngopi Bogor, Indonesia - Ismartaya, Ismartaya; Hikmat Maulana, Lucky; Simanjuntak, Wildaria; Kartini, Tini (International Journal of Science, Technology & Management, 2023)
In the current era of globalization the business world is growing day by day so companies will not be separated from competition and are required to provide a good marketing system. The problem of product quality, service quality and customer satisfaction is the determining factor so it needs to be investigated. The sampling technique used was purposive sampling with a total sample of 60. The data collection technique used a questionnaire that had been tested for validity, reliability test, and classical assumption test. The data analysis method used was multiple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis. A hypothesis test was also conducted using the F test method and the t test. The results showed that simultaneously and partially product quality, service quality had a positive and significant effect on consumer satisfaction. It is recommended to evaluate to find information that makes consumers comfortable and satisfied.